Analysis from the Capabilities Approach of the Contributions of Service Learning for Students of a South African University - Monge-Hernández, Carmen (2020)
This article addresses the contradiction between training oriented to technical capabilities and training focusing on socially valued capabilities. Its purpose is to value pedagogical experiences that contribute to the expansion of valuable professional skills for students and society. Based on the capabilities approach for human development (CAHD), we analyzed the contribution to the expansion of student capacities that is promoted by curricular service-learning (ApS) practices, developed at the University of the Free State (UFS), South Africa. The analysis is based on the application of the following qualitative techniques: documentary review, participant observation, and semi-structured interviews. The results make visible the expansion of socially valued capacities in the students and serve as a guide for recommendations of institutional changes for curricular integration and institutional valorization of ApS, as a transforming formative experience.